Social Network Trajectories in Myocardial Infarction Versus Ischemic Stroke - Dhand, Amar (J Am Heart Assoc, 2018)
BACKGROUND: Changes in social networks are rarely examined before and after various diseases because of insufficient data. CHS (The Cardiovascular Health Study) offers an opportunity to compare social network trajectories surrounding well‐adjudicated myocardial infarction (MI) or stroke events. We tested the hypothesis that social networks will be stable after MI and decrease after stroke. METHODS AND RESULTS: We examined trajectories of the Lubben Social Network Scale score (LSNS, range 0–50) before and after vascular events over 11 years. The LSNS assesses engagement in family networks, friends’ networks, and social supports. We used a linear mixed model with repeated measures and fixed effects to compare the change in social network score before and after events in 395 people with MI and 382 with ischemic stroke. Over a mean of 12.4 years of follow‐up for MI and 11.1 years for stroke, we examined an average of 4 social network scores for each participant. We controlled for sociodemographics, baseline cognitive function, and comorbidities. The participants’ mean age was 73.5, 51% were women, and 88% were non‐Hispanic white. After MI, the social network trajectory remained stable compared with the baseline trajectory (−0.06 points per year, adjusted P=0.2356). After stroke, the social network trajectory declined compared with the baseline trajectory (−0.14 points per year, adjusted P=0.0364). CONCLUSIONS: Social networks remained stable after MI and declined after stroke. This small and persistent decline after adjustment for potential confounders is notable because it deviates from stable network trajectories found in CHS participants and is specific to stroke.